Rat and poultry feeding studies with soybean meal produced from imidazolinone-tolerant (CV127) soybeans. (February 2016) - He, Xiaoyun; de Brum, Paulo A.R.; Chukwudebe, Amechi; Privalle, Laura; Reed, Andrew; Wang, Yanqing; Zhou, Cui; Wang, Cuiyan; Lu, Jing; Huang, Kunlun; Contri, Daniela; Nakatani, Andreia; et al.
Abstract: The safety and nutritional properties of CV127 soybeans were evaluated in rat and broiler feeding studies. Some episodic differences were observed between rats fed CV127, Conquista, and the standard diet for the endpoints examined. None of these differences were considered treatment related, adverse, or biologically meaningful. In general, birds fed diets containing CV127, Conquista, or Monsoy 8001 showed no significant differences in growth and performance response variables. Chickens fed diets containing Coodetec 217 had lower body weight and weight gain for all developmental periods compared to CV127, but no significant differences were found in feed conversion for the two diets during any development period. The results of both feeding studies demonstrate that CV127 soybeans are as safe, wholesome, and nutritionally valuable as the other soybean meals tested, including those varieties for which histories of safe use have been established and well documented. Highlights: No significant differences were observed in body weight change for male or female rats when comparing CV127 versus control. No treatment related effects were found between rats fed CV127 versus control for hematology or serum chemistry values. Broilers fed a diet comprised of CV127 yielded growth performance at least equivalent to control and reference diets.